2010
DOI: 10.1159/000239064
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Acoustic Parameters and Voice Handicap Index in Dysphonic Teachers

Abstract: Objective: The aim of this study was to investigate the relationship between acoustic analysis and biopsychosocial implications of voice problems, evaluated by the Voice Handicap Index (VHI). Materials and Methods: The study comprised 120 female teachers with voice disorders, evaluated by videolaryngostroboscopy. 60.8% of this group were diagnosed as having functional dysphonia and 39.2% had dysphonia with benign vocal fold masses (nodules and polyps). The controls consisted of 30 euphonic women. The correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 49 publications
0
14
1
6
Order By: Relevance
“…Schindler et al (8) suggested that the physical score of VHI in patients with vocal cord nodules was correlated with the jitter (Jitt), shimmer (Shim) and normalized noise energy (NNE). In addition, findings of other studies demonstrated the functional and emotional scores, but not the physical score, which in VHI were associated with Jitt and Shim (9). Thus, the subjective perception of voice handicap cannot be replaced and predicted with findings in objective detection.…”
Section: Discussionmentioning
confidence: 85%
“…Schindler et al (8) suggested that the physical score of VHI in patients with vocal cord nodules was correlated with the jitter (Jitt), shimmer (Shim) and normalized noise energy (NNE). In addition, findings of other studies demonstrated the functional and emotional scores, but not the physical score, which in VHI were associated with Jitt and Shim (9). Thus, the subjective perception of voice handicap cannot be replaced and predicted with findings in objective detection.…”
Section: Discussionmentioning
confidence: 85%
“…Hałas jest jednym z wielu czynników środowiska pracy, który wpływa na powstawanie dolegliwości narządu gło-su [1][2][3][4][5][6][7]. Kiedy rośnie poziom dźwięku A tła akustycznego, nauczyciele i wykładowcy zwiększają poziom natę-żenia głosu [4,5,8].…”
Section: Wstępunclassified
“…Kiedy rośnie poziom dźwięku A tła akustycznego, nauczyciele i wykładowcy zwiększają poziom natę-żenia głosu [4,5,8]. Długotrwałe obciążanie i forsowanie narządu głosu może przyczynić się do powstawania chorób zawodowych narządu głosu, takich jak wtórne zmiany przerostowe fałdów głosowych oraz niedowład mię-śni wewnętrznych krtani z wrzecionowatą niedomykalnością fonacyjną głośni i trwałą dysfonią [1][2][3]6,9].…”
Section: Wstępunclassified
“…Powstają one w wyniku nadmiernego obciążenia głosu, które jest spowodowane hała-sem w szkole i koniecznością mówienia przez nauczycieli głosem podniesionym (o większym natężeniu) (4)(5)(6)(7)(8)(9).…”
Section: Wstępunclassified